If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7=3(23-x)+2(x-2)
We simplify the equation to the form, which is simple to understand
7=3(23-x)+2(x-2)
Reorder the terms in parentheses
7=+(+69-3x)+2*(x-2)
Remove unnecessary parentheses
+7=+69-3x+2+*(+x-2+)
Reorder the terms in parentheses
7=+69-3x+(+2x-4)
Remove unnecessary parentheses
+7=+69-3x+2x-4
We move all terms containing x to the left and all other terms to the right.
+3x-2x=+69-4-7
We simplify left and right side of the equation.
+1x=+58
We divide both sides of the equation by 1 to get x.
x=58
| 7=t^2-6t | | -3p-48=0 | | 3r+11=2-3(3r+3) | | -7+x=-3x+25 | | 3ln(5x+4)=22 | | 4(4x-9)-6=4(x-4)+46 | | 16x^2-7t=17t-9 | | 36-6x=14+5x | | 2u^2+13u+15=0 | | (4x^2)+4x+(4y^2)-32y-335=0 | | 4x^2-147=0 | | (7/2)^-1=-1/7x | | (X-7)/2=(5-x)/4 | | 54-8x=18+10X | | 3(3x+5)=60 | | 8(3t-5)+12=-8 | | 54-8x=18+10 | | 16x^3-132x+252=0 | | 2+3(x+1)=9-3+2x | | 4(x+7)=-2x+34 | | x^3+8x^2+20x=0 | | 8x^2+5x+25=0 | | 5x+2=14+6X | | 13(17-x)=15(x+1) | | -7(1-2x)+8=-83 | | g(x)=3(5)x | | 4r^2-r+3=0 | | 3v+6=9-3(2v-2) | | x+3(x+6)=4(2x+1) | | 4(3z-3)=18 | | (2x-17)/5=-5 | | -11=3(v-7)-8v |